Business Model Canvas Analysis for Honey Business Development at Situak Ni Loba Siarsikarsik Social Forestry Business Group, Lumban Julu District, Toba Regency - Eva Theresia Gurusinga; Oding Affandi; Rahmawaty Rahmawaty; Rita F. Dalimunthe (Jurnal Ilmu Kehutanan, 2024)
Honey has numerous benefits and considerable potential for development within the Social Forestry Business Group (KUPS). In 2020, honey consumption in Indonesia increased to 60 grams per capita per year, leading to growth in the honey bee business. However, more research is needed to be done on developing business strategies for KUPS in North Sumatra Province. Therefore, this research aimed to formulate development strategies for the honey bee business in Situak Ni Loba Siarsikarsik KUPS, Toba Regency, using the Business Model Canvas (BMC) method. This descriptive qualitative research collected data through direct observation, interviews, discussions, and literature research to map the business model through the nine main elements of BMC, namely customer segments, value propositions, channels, customer relationships, revenue flows, main resources, activities, partnerships, and cost structure. The best strategy identified was to increase the value proposition, expand the strategic partner network, and improve market access. The findings highlighted the need to determine the specialty of the honey produced by the KUPS compared to other products, find cooperation partners for investment, and utilize technology and marketplaces to expand market share.